2011
DOI: 10.1007/s11434-010-4210-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of surface soils across the southern Tarim Basin and their relationship with climate and source materials

Abstract: The magnetic susceptibility (χ) of surface soils on the Chinese Loess Plateau (CLP) has strong positive correlation with mean annual precipitation. It is widely accepted that ultrafine magnetite/maghemite grains produced during pedogenesis are responsible for the enhancement of χ, and loess χ on the CLP has been widely used as a proxy for the intensity of the East Asian summer monsoon. However, few works have investigated mechanisms for the enhancement of χ in the case of surface aeolian sediments in westerly-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Wei et al (2013) attributed magnetic enhancement to the stronger pedogenesis at increased elevation regions. Furthermore, a good correlation between MS and elevation has been observed in the case of surface sediments of loessic sands and loess from the Tarim Basin (Zan et al, 2011).…”
Section: Dca Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Wei et al (2013) attributed magnetic enhancement to the stronger pedogenesis at increased elevation regions. Furthermore, a good correlation between MS and elevation has been observed in the case of surface sediments of loessic sands and loess from the Tarim Basin (Zan et al, 2011).…”
Section: Dca Resultsmentioning
confidence: 81%
“…Wei et al () attributed magnetic enhancement to the stronger pedogenesis at increased elevation regions. Furthermore, a good correlation between MS and elevation has been observed in the case of surface sediments of loessic sands and loess from the Tarim Basin (Zan et al, ). However, other research (Guo et al, ; Wei et al, ) argued that the magnetic properties were mainly controlled by wind intensity and dust provenance and basically had nothing to do with elevation.…”
Section: Discussionmentioning
confidence: 90%
“…For the section in Jiuzhoutai, Lanzhou, where the zonal soils are also sierozems, the annual precipitation is about 300 mm and the annual temperature is 11.3°C,  and  fd % are about 9×10 and <4 respectively. In northwestern China, there is a linear relationship between altitude and the grain size of loess deposits [64]. Therefore, less input of coarse magnetic grains is expected at higher altitude.…”
Section: Discussionmentioning
confidence: 99%
“…The good relationship between precipitation and pedogenesis (Blundell et al, 2009;Gao et al, 2018;Heller et al, 1993;Liu et al, 2005;Lü et al, 1994;Lyons et al, 2010;Maher, 1998;Maher & Thompson, 1995) has resulted in rock magnetic methods becoming widely used to reconstruct past climatic conditions (Heller & Tungsheng, 1984;Maher, 1998;Evans & Heller, 2003). A recent rock magnetic study of eolian sand and loess samples from the NE Tibetan Plateau demonstrated that the surface loess deposits exhibit significant variations in magnetic properties between the westerlies-influenced and Asian summer monsoon-influenced regions (Zan et al, 2011(Zan et al, , 2015. In the areas influenced by the moist Asian summer monsoon regime, surface soil samples generally have high values of anhysteretic susceptibility (χ ARM ) and magnetic susceptibility (χ) and its frequency dependence (χ fd ), indicating the occurrence of stronger pedogenesis due to the abundant precipitation.…”
Section: Introductionmentioning
confidence: 99%